Confirmatory factor analysis of the teaching strategy for HOTs and LOTs Inventory in the Malaysian context - Che Md Ghazali, Nor Hasnida; Md Hassan, Nurulhuda; Mat Rabi, Norfishah; Zaini, Syaza Hazwani (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Promoting students’ higher order thinking skills is now becoming more important in an education system. An effective teaching strategies are required to teach those skills to students. Hence, a valid, reliable and practical instrument is needed to evaluate teaching strategies used in promoting students’ higher order thinking skills (HOTs) and lower order thinking skills (LOTs). The aim of this study is to explore different factor structure of the teaching strategies scale by using the secondorder Confirmatory Factor Analysis. The instrument is adapted from an instrument developed by Gulistan (2016) to suit with the Islamic education teachers in the Malaysian context. 220 primary school teachers teaching Islamic education subject was selected randomly from one of the state in Malaysia. The content validity is assessed by a group of experts, and the construct validity is measured by Confirmatory Factor Analysis. The reliability of the instrument is measured by the alpha coefficient reliability or Cronbach Alpha. Results indicated that the teaching strategies inventory is a valid and reliable scale. The measurement model is validated with two factors (‘Acquiring Knowledge’ and ‘Applying Knowledge and Reflection on Knowledge’). This study provides support for using a valid instrument in evaluating teaching strategies used by Islamic education teachers in primary level in real study later.